Active management of third stage of labor - Thapa, Meena; Saha, Rachana; Pradhan, Sumita; Thakur, Sushil; Rana, Archan Shamsher (Nepal Journal of Obstetrics and Gynaecology, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Objective: Overall objective of the study was to see effects of active management of third stage of labour (AMSTL) with oxytocin. Specific objective of the study was to look for incidence of Post-Partum Haemorrhage (PPH), length of 3rd stage, incidence of retained placenta and average blood loss. Methodology: A hospital based prospective, descriptive, observational study was carried out from 1st July 2005 to 30th June 2006 at department of Obstetrics and Gynaecology, Kathmandu Medical College Teaching Hospital (KMCTH). All patients undergoing vaginal delivery excluding twins, polyhydraminios and instrumental deliveries were included in the study. The active management of 3rd stage included administration of 10 units IU of oxytocin, early cord clamping, controlled cord traction and uterine massage. Blood loss was estimated by visual inspection and measured by jar pressed against perineum. Result: Total number of deliveries during the study period was 530. There were 13 cases of PPH. Incidence of PPH was 2.4%. There were six cases each of uterine atony and genital tract trauma. One case was of retained placenta requiring Manual Removal (MRP). Average third stage duration was less than 5 minutes. Average blood loss was 90 ml. In 2 cases the third stage lasted more than 30 mins. Conclusion: Active management of 3rd stage of labour reduces the incidence of PPH from uterine atony, reduces the duration as well as average blood loss during third stage.condition. Key words: Labor analgesia; epidural, combined spinal epidural; complications, dural puncture, postdural puncture headache (PDPH); prevention. doi:10.3126/njog.v1i2.1490 N. J. Obstet. Gynaecol Vol. 1, No. 2, p. 25 - 27 Nov-Dec 2006